Store and neighborhood differences in retailer compliance with a local staple foods ordinance - Caitlin E. Caspi; Megan R. Winkler; Kathleen M. Lenk; Lisa J. Harnack; Darin J. Erickson; Melissa N. Laska (BMC, 2020)
Abstract Background Policies to improve healthy food retail have been recognized as a potential means of reducing diet-related health disparities. The revised 2014 Minneapolis Staple Foods Ordinance instituted minimum stocking standards for healthy, staple foods. The objective of this study was to examine retailer compliance with the policy, and whether compliance varied by neighborhood and store characteristics. Methods In this natural experiment, audits were conducted annually pre- and post-ordinance (2014-2017) in 155 small/nontraditional stores in Minneapolis, MN and a comparison city (St. Paul, MN). Compliance measures for 10 product categories included: (1) met requirements for ≥8 categories; (2) 10-point scale (one point for each requirement met); and (3) carried any item in each category. Store characteristics included store size and ownership status. Neighborhood characteristics included census-tract socioeconomic status and low-income/low-access status. Analyses were conducted in 2018. Results All compliance measures increased in both Minneapolis and St. Paul from pre- to post-policy; Minneapolis increases were greater only for carrying any item in each category (p < 0.01). In Minneapolis, corporate (vs. independent) stores were generally more compliant. No differences were found by neighborhood characteristics. Conclusions Overall trends suggest broad movement among Minneapolis stores towards providing a minimum level of staple foods. Increases were greater in corporate stores. Trends do not suggest neighborhood-level disparities in compliance. Study registration ClinicalTrials.gov NCT02774330, retrospectively registered May 17, 2016.